THE ROLE OF MINIMALISM IN MODERN FINE ARTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This paper explores the significance and influence of minimalism in modern fine arts, emphasizing its aesthetic principles, philosophical foundations, and cultural impact. Minimalism, characterized by simplicity, reduction of form, and deliberate use of space, emerged as a reaction against the complexity and emotional intensity of previous art movements. By analyzing key works and artists associated with minimalism, the study reveals how minimalism challenges traditional notions of art, focusing instead on purity, clarity, and the viewer’s personal interpretation. Furthermore, the paper discusses how contemporary artists adopt minimalist strategies to address modern themes such as consumerism, identity, and digital abstraction. The role of minimalism in shaping artistic discourse and redefining the boundaries of visual expression continues to grow, making it a vital component of today’s art landscape.